Examining the Relationship between Technological Infrastructure and the Quality of Online Education Programs - Arkam Lahiya; Sabil Mokodenseho (Westscience Press, 2023)
This research paper investigates the relationship between technological infrastructure and the quality of online higher education programs in Sukabumi, Indonesia. The study utilizes a mixed-methods research design, incorporating quantitative surveys and qualitative interviews to gather comprehensive data. The population of interest includes students, instructors, administrators, and policymakers involved in online education. The findings from the surveys reveal the current state of technological infrastructure and participants' perceptions of program quality. The qualitative analysis of interviews uncovers themes related to the impact of technological infrastructure on instructional design, student-teacher interaction, resource access, assessment methods, and administrative processes. The results and analysis provide valuable insights into the strengths, weaknesses, challenges, and opportunities concerning technological infrastructure in Sukabumi's online higher education sector.